Fujairah, Vereinigte Arabische Emirate: Ausgrabungen bronzezeitlicher Befunde und Survey von intakten Kulturlandschaften - Pfeiffer, Kristina (e-Forschungsberichte des DAI, 2023)
In spring 2016 an initial season of joint fieldwork between the Orient department and the Fujairah Tourism & Antiquities Authority was conducted in the Emirate of Fujairah. The threefold season consisted of a rescue excavation of an endangered cairn site, a research excavation of a building structure of the Wadi Suq period (c. 1900–1300 BC) and a cultural landscape survey in the mountainous region and along the coast. The survey was conceptualized with the aim to detect potential Bronze Age settlement sites in naturally favored landscape zones.